KECERDASAN EMOSIONAL DAN PENINGKATAN SELF-EFFICACY WIDYAISWARA - Martatik Martatik (Penamas, 2019)
ABSTRACT This study will asses the effect of emotional intelligence to self efficacy of instruture in Ministry of Religious Affairs in carrying out the task of educating, teaching and training, using a survey toword trainers of Ministry of Religious Affairs. This survey use multiple regretion for data analysis. The result shows that 1) There is significant influence of interpersonal relationships, and general mood on the self efficacy 2) there is no significant influence of intrapersonal relationship, adabtibelity and stress management on self efficacy.